2003
DOI: 10.1002/em.10176
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of 8‐hydroxy‐2‐deoxyguanosine and 1‐hydroxypyrene in coke‐oven workers

Abstract: Coke-oven workers (COWs) are occupationally exposed to high concentrations of polycyclic aromatic hydrocarbons (PAH). Urinary 8-hydroxy-2-deoxyguanosine (8-OH-dG) and 1-hydroxypyrene (1-OHP) are biological markers of oxidative DNA damage and PAH metabolism, respectively. We investigated the relationship between urinary 8-OH-dG and 1-OHP in 217 Taiwanese COWs, 55 topside-oven, and 162 sideoven workers. For topside-oven workers, mean 8-OH-dG and 1-OHP concentrations (ng/ml +/- SD) were 13.8 +/- 12.0 and 93.5 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 32 publications
3
47
0
Order By: Relevance
“…Similar findings were reported by a study conducted in five European countries (31), and by a study involving men on high fruit and vegetable diets (32). A study involving coke-oven workers who took vitamin supplements showed that the excretion of 8-oxodG adducts was decreased compared to those workers that took no vitamins (33). However, the study did not include direct measurements of plasma vitamin levels were not measured.…”
Section: Discussionsupporting
confidence: 78%
“…Similar findings were reported by a study conducted in five European countries (31), and by a study involving men on high fruit and vegetable diets (32). A study involving coke-oven workers who took vitamin supplements showed that the excretion of 8-oxodG adducts was decreased compared to those workers that took no vitamins (33). However, the study did not include direct measurements of plasma vitamin levels were not measured.…”
Section: Discussionsupporting
confidence: 78%
“…These findings conflict with the generally accepted consensus of opinion that an intake of fruits and vegetables by healthy individuals leads to a reduction of oxidative DNA damage [35]. A study involving coke-oven workers who took at least one multi vitamin pill showed that the urinary excretion of 8-oxodG adducts was decreased compared to those workers that took no vitamins [36]. In a separate study the level of M 1 dG adducts was found to be decreased in human colorectal mucosa DNA from men that had a diet with high levels of fruit and vegetables [37].…”
Section: Discussionmentioning
confidence: 75%
“…Notably, most previous studies measured urinary and/or blood biomarkers at the end of a work shift as a single measurement (5,7,26,32,33). These readings may be affected by the known circadian variation in certain biomarker level (e.g., 8-oxodG; ref.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary1-OHP was determined by a high performance liquid chromatography (HLPC) with the fluorescence detection method (26). Briefly, 20 mL of 0.1 mol/L acetate buffer (pH 5.0) and 20 AL glucoronidase-arylsulfatase (134,600 unit/mL; Sigma) were added to 10 mL urine and incubated for 4 h at 37jC in an electronically controlled rotary shaking bath.…”
Section: Methodsmentioning
confidence: 99%